(untitled) (Hekima Review, 2010)
John Perry states from the beginning of his book that although it has been abolished for more than two hundred years in many of the western countries, slavery persists today in many places in our world. The author notes that like a dangerous virus, slavery has mutated into elusive new form (11). Perry’s book is divided in two parts. The first part is entitled Traditional slavery and the Catholic Church. This first part comprises four chapters that focus on the definition of the terms, a biblical review of the place of slavery in the New Testament, the Catholic response to slavery and the development of the Catholic doctrine on slavery.